Geografia e saberes modernos: a inserção da complexidade nos discursos geográficos - Pelegrini, Djalma Ferreira (2008)
The emergence of recent approaches, identified together with the term complexity , which seek to understand reality as a result of the multiple action of various factors, and which oppose the traditional theoretical standards in use in the various areas of knowledge, are provoking the development of endless research in a different focus in Geography. This study tries to verify up to what point these approaches to complexity offer theoretical, referential contributions for studies made in this field. For this reason, it became necessary to establish the distinction between the notion of method, or discovery logic, approaches and research procedure. Following this came the analysis of books, texts and experiments which expound the theme of complexity in Geography. The similarity between some procedures identified with complexity in relation to the customary expressions of geographers, suggested as an explanation for the wide acceptance of these approaches, was verified. It was also possible to distinguish, in general terms, two types of expression, the results of the application of complexity approaches in Geography. The first corresponds with those who make use of the original theories of natural science in the interpretation of geographic phenomena based on computer models. The second can be identified by the pre-eminence of the philosophic, historic, metascientific or literary presentations and by frequently using the term paradigm , which plays an essential part in the theoretical elaboration of Edgar Morin, the principal influence for this source.